The Electronic Digital Computer in Indian Forestry - Chacko, V. J. (Indian Forester, 1967)
In this paper, the basic components, operation and potentialities of a digital computer are outlined and the major effect on forestry development indicated. The better computational facilities provided by an electronic computer can stimulate developments which can have a revolutionary impact on Indian Forestry. The computer can lead to greatly increased all round competence in tbe application of known methods, both in speed and in comprehensivences.It can increase the output of the departments and give a new dimension to the research efforts. It can also be utilized to evolve new techniques and for improving current methods and practices. However, the computer, naturally, imposea also certain obligations on the forest workers.